2020
DOI: 10.3390/ijms21249651
|View full text |Cite
|
Sign up to set email alerts
|

Monosomy 3 Influences Epithelial-Mesenchymal Transition Gene Expression in Uveal Melanoma Patients; Consequences for Liquid Biopsy

Abstract: Despite outstanding advances in diagnosis and the treatment of primary uveal melanoma (UM), nearly 50% of UM patients develop metastases via hematogenous dissemination, driven by the epithelial-mesenchymal transition (EMT). Despite the failure in UM to date, a liquid biopsy may offer a feasible non-invasive approach for monitoring metastatic disease progression and addressing protracted dormancy. To detect circulating tumor cells (CTCs) in UM patients, we evaluated the mRNA expression of EMT-associated transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 77 publications
1
13
0
1
Order By: Relevance
“…Both M3 and 8q gain are related to other poor prognostic factors such as ciliary body involvement, epithelioid cells, large tumor basal diameter, high mitotic count, and closed connective tissue loops [ 33 ]. Given the high degree of correlation between M3 and Class 2 expression profile, M3 is a reliable prognostic marker [ 7 , 14 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both M3 and 8q gain are related to other poor prognostic factors such as ciliary body involvement, epithelioid cells, large tumor basal diameter, high mitotic count, and closed connective tissue loops [ 33 ]. Given the high degree of correlation between M3 and Class 2 expression profile, M3 is a reliable prognostic marker [ 7 , 14 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lukenda et al demonstrated that KIT -positive patients (cutoff >10%, using 3-amino-9-ethylcarbazole chromogen) had a 4.13-fold higher risk ( p = 0.017, 95% CI 1.289 to 13.223) of lethal outcome and shorter overall ( p = 0.005) and disease-free survival ( p = 0.009) in comparison with KIT -negative cases [ 21 ]. Accordingly, we found KIT among the top-ranked genes upregulated in M3 samples [ 23 ]. Recently, liquid biopsy proteomics data were published, revealing the biomarkers associated with metastatic risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations